Kemerdekaan Pers di Indonesia pada Masa Pemilu 2024 ditinjau dari Teori Keadilan Hukum - Az Zahra, Husna Meila Nahdah; asmorojati, anom wahyu (Wajah Hukum, 2025)
This study aims to determine the independence of the press in Indonesia during the 2024 elections from the perspective of legal justice theory and to analyze the relationship between factors influencing press independence in Indonesia during the 2024 elections and legal justice theory. The method used in this study is normative legal research, which examines issues based on applicable regulations and literature studies. The results of the study show, first, that press freedom in Indonesia during the 2024 elections does not yet meet the principles of legal justice as stated by John Rawls. This is evident in the imbalance in news coverage, which results in news reports and journalistic products produced by some media outlets being unfair and far from balanced, thereby harming other candidates. In addition, the public is also disadvantaged because freedom in obtaining accurate and fair information has not been achieved as it should be. The existence of this imbalance in reporting shows that the press has not been able to carry out its function freely and fairly as a provider of information to the public. Second, the factors that influence press freedom in Indonesia during the 2024 elections show that there is still control by financiers (media company owners) over the press and that there are no firm regulations regarding the enforcement of press freedom, which can lead to violations of the principles of legal justice.